1995
DOI: 10.1037/0033-2909.118.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of chronic pain: An evaluative comparison of restrictive and comprehensive models.

Abstract: The authors compare theoretical perspectives of chronic pain using a restrictive comprehensive categorization. Four of the perspectives (mind-body dualism, psychological, radical operant--behavioral, and radical cognitive) are categorized as restrictive. The other 4 perspectives (International Association for the Study of Pain, gate control, nonradical operant--behavioral, and cognitive-behavioral) that incorporate multiple facets are categorized as comprehensive. On the basis of empirical support, practical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 102 publications
(144 reference statements)
3
50
0
Order By: Relevance
“…In addition, an examination of the pain treatments received by these individuals indicated that their pain problems were often overlooked and under-treated (Engel et al, 2002(Engel et al, , 2003. That participants in Schwartz et al's (1999) study recognize that both psychological and physical factors can change their pain experience is consistent with cognitive-behavioural theories and contemporary biopsychosocial theories of pain (Novy et al, 1995). These theories hypothesize that how individuals respond to and cope with pain affects their adaptation (adjustment) to chronic pain.…”
Section: Introductionsupporting
confidence: 48%
See 1 more Smart Citation
“…In addition, an examination of the pain treatments received by these individuals indicated that their pain problems were often overlooked and under-treated (Engel et al, 2002(Engel et al, , 2003. That participants in Schwartz et al's (1999) study recognize that both psychological and physical factors can change their pain experience is consistent with cognitive-behavioural theories and contemporary biopsychosocial theories of pain (Novy et al, 1995). These theories hypothesize that how individuals respond to and cope with pain affects their adaptation (adjustment) to chronic pain.…”
Section: Introductionsupporting
confidence: 48%
“…To the extent that catastrophizing cognitions contribute to depressive symptoms specifi cally, and lower quality of life in general (and current biopsychosocial models of chronic pain hypothesize such a causal association (Novy et al, 1995), then the current fi ndings suggest that one of the most effective strategies for improving quality of life in adults with CP-related pain would be to help Turk, 2002), which teaches people to identify catastrophizing cognitions and replace them with more realistic and reassuring thoughts. There is a great deal of empirical support for the effi cacy of such treatments for reducing disability and depression among persons who present with pain as a primary complaint (Morley et al, 1999), although the effi cacy of such treatments for persons with CP-related pain or cognitive impairment have yet to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Some may say that there is no single cognitive behavioral model of this type -this is a point we address. It is clear that there is what is called the "cognitive behavioral perspective" that has presented a framework for the therapy approach to chronic pain since its inception, 73 is regarded as a model, 66 and the term "cognitive behavioral model" certainly is used. 34 We intend TCB in this same vein.…”
Section: Psychological Flexibility and Chronic Pain 25mentioning
confidence: 99%
“…Individual psychological differences are recognized as affecting the course and outcome of a wide range of severe and debilitating chronic illnesses [1][2][3][4] . First-person accounts [5,6] , case reports [7] , qualitative and quantitative research [8,9] collectively suggest that this is also true in schizophrenia.…”
Section: Copyright © 2007 S Karger Ag Baselmentioning
confidence: 99%